Nose-to-Brain Drug Delivery of Donepezil Loaded Lipid-Based Nanoemulsion for Alzheimer - Pannu, Anuradha; Shah, Tora; Bhutada, Pooja Ganesh; Sharma, Rahul; Sharma, Sachin Kumar; Kulkarni, Parag Arun; Nath, Junmoni; Chinchole, Pratik Ashokrao (Journal of Neonatal Surgery, 2025)
Background: Nose-to-brain drug delivery offers a promising alternative to bypass the blood-brain barrier and directly target the central nervous system. Donepezil, a commonly used drug for Alzheimer’s disease, suffers from low oral bioavailability and delayed therapeutic action. Therefore, an optimized nanocarrier system is essential to improve brain targeting and enhance treatment efficacy. Objective: This study was designed to develop and optimize a Donepezil-loaded lipid-based nanoemulsion to enhance nose-to-brain delivery and improve therapeutic outcomes in Alzheimer’s disease. Methods: A Box-Behnken Design (BBD) was utilized to optimize three independent variables: drug-to-lipid ratio (1:2 to 1:6), surfactant concentration (1–2% w/v), and stirring speed (1500–2500 rpm). The critical quality attributes evaluated were particle size (R1), drug entrapment efficiency (R2), and drug loading (R3). Glyceryl Monostearate (GMS) and Tween 80 were selected based on solubility and hydrophilic-lipophilic balance (HLB). Seventeen formulations were developed and analyzed using response surface methodology. Results: Optimized Formulation Extra Batch 18 exhibited a particle size of 160.12 nm, drug entrapment efficiency of 80.75%, and drug loading of 19.98%, with a desirability score of 0.977. All observed results were found to be within ±5% variation from predicted values. ANOVA results confirmed statistical significance (p < 0.05) with a non-significant lack of fit, indicating model adequacy and predictive reliability. Graphical analysis through 3D surface plots and predicted vs. actual plots supported the optimization outcomes. Conclusion: The optimized lipid-based nanoemulsion of Donepezil showed potential for improved nose-to-brain delivery, enhancing brain bioavailability and minimizing systemic side effects. This formulation presents a promising therapeutic approach for Alzheimer’s disease management